Distinctiveness in combat sport aesthetics - Jason Holt (Acta Universitatis Carolinae: Kinanthropologica)
According to some philosophers, sports where athletes actively struggle against their opponents are aesthetically enhanced because of the increased potential for drama arising from dynamics of social interaction. I argue that combat sports further increase the potential of such dramatic aesthetic appeal. In contrast to the comparatively abstract struggles of team sports, suggesting a more detached Kantian aesthetic, combat sports involve competitive struggles that are less abstract and more primal, suggesting a more engaged Deweyan aesthetic. I also argue for a hierarchy of primal appeal within combat sports from the minimally constrained primal appeal of mixed martial arts to the more abstract, less primal appeal of fencing. Between these extremes, grappling sports (e.g., wrestling, judo, and jiu jitsu,) have a more primal (and intimate!) but less dramatic appeal than striking sports (e.g., boxing, kickboxing, and taekwondo). I conclude by raising and resolving an apparent paradox suggested by my account.